Cohort study of THRIVE predicting adverse outcomes in acute ischemic stroke of the anterior circulation and posterior circulation after 3 months and 1 year of follow-up. (February 2022) - Chen, Li-Li; Yan, Shuang-mei; Wang, Wen-Ting; Zhang, Sai; Liu, Hui-Miao; Yuan, Xiao-Yang; Yang, Xu; Gu, Ping
Highlights: The predictive effect of THRIVE on anterior and posterior circulatory stroke. THRIVE can well predict the short-term and long-term prognosis of different circulatory stroke. THRIVE has the same predictive effect on two circulatory systems. Abstract: Purpose: To evaluate the difference of Totaled Health Risks In Vascular Events (THRIVE) in predicting adverse outcomes in acute ischemic stroke (AIS) of the anterior circulation and posterior circulation at 3-month and 1-year follow-up. Methods: A total of 858 patients with AIS were followed up for 3 months and 1 year, and their data prospectively collected. The occurrence of death or moderate to severe disability (modified Rankin Scale ≥ 3 points) was regarded as the endpoint. MedCalc software was used to create the THRIVE receiver operating characteristic curve. The area under the curve (AUC) was calculated to compare the THRIVE scale in predicting adverse outcomes in AIS of the anterior and posterior circulation and compare the differences. Results: At 3-month follow-up, the AUC of THRIVE was 0.685 (95% CI 0.644–0.724) for AIS of the anterior circulation and 0.709 (95% CI 0.647–0.765) for AIS of the posterior circulation. The area difference between them was 0.0235 (95% CI −0.0728–0.120, P = 0.6330[>0.05]). The AUC of THRIVE for AIS in the anterior circulation at 1 year was 0.701 (95% CI 0.660–0.740), and that for AIS in the posterior circulation at 1 year was 0.747 (95% CI 0.687–0.800). The area difference between them was 0.0458 (95% CI −0.0489–0.140, P = 0.3436 [>0.05]). The difference was not statistically significant. Conclusion: THRIVE can well predict the short-term and long-term adverse prognosis of AIS in the anterior and posterior circulation and has the same predictive effect.